2008
DOI: 10.1107/s1600536808019120
|View full text |Cite
|
Sign up to set email alerts
|

4-Chloro-N-(2,6-dimethylphenyl)benzamide

Abstract: The conformations of the N—H and C=O bonds in the structure of the title compound (N26DMP4CBA), C15H14ClNO, are anti to each other, similar to that observed in N-phenyl­benzamide, N-(3,4-dimethyl­phen­yl)benzamide, N-(2,6-dichloro­phen­yl)benzamide and other benzanilides. There are three mol­ecules in the asymmetric unit of N26DMP4CBA. The central amide group is tilted with respect to the benzoyl ring by 45.2 (1)° in mol­ecule 1, 21.2 (2)° in mol­ecule 2 and 14.9 (2)° in mol­ecule 3. The dihedral angles betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
5
3
0
Order By: Relevance
“…The conformations of N-H and C═O bonds in the amide groups are trans to each other ( Fig. 1), similar to that observed in other benzamides and benzanilides (Gowda et al, 2003(Gowda et al, , 2008. Also, the conformations of the amide O atoms are syn to the ortho amino groups in the benzoyl rings.…”
Section: Related Literaturesupporting
confidence: 81%
See 1 more Smart Citation
“…The conformations of N-H and C═O bonds in the amide groups are trans to each other ( Fig. 1), similar to that observed in other benzamides and benzanilides (Gowda et al, 2003(Gowda et al, , 2008. Also, the conformations of the amide O atoms are syn to the ortho amino groups in the benzoyl rings.…”
Section: Related Literaturesupporting
confidence: 81%
“…For applications of polyamides, see: Kang et al (2001). For related structures, see Gowda et al (2003Gowda et al ( , 2008. For graph-set notation, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The two aromatic rings are inclined at 3.32 (3)°. Bond distances within the molecule are normal (Allen et al 1987) and similar to those observed in comparable structures (Gowda et al 2008;Zhou & Zheng 2007).…”
Section: S1 Commentsupporting
confidence: 76%
“…For the graph-set analysis of hydrogen-bond patterns, see: Bernstein et al (1995). For related structures, see: Gowda et al (2008); Zhou & Zheng (2007); Khan et al (2010). Benzamide derivatives are frequently used in the synthesis of new and effective anti-convulsant agents, see: Clark et al (1988); Leander et al (1988); Diouf et al (1997).…”
Section: Related Literaturementioning
confidence: 99%
“…In the present work, the structure of 2-chloro-N-(3,5-dimethylphenyl)-benzamide (N35DMP2CBA) has been determined to explore the substituent effects on the solid state structures of benzanilides (Gowda et al, 2003(Gowda et al, , 2008a. The conformations of N-H and C=O bonds in the amide group of N35DMP2CBA are trans to each other ( Fig.1), similar to that observed in 2-chloro-N-(3,5-dichlorophenyl)-benzamide(N35DCP2CBA) (Gowda et al, 2008a), 2-chloro-N-(phenyl)-benzamide (NP2CBA) (Gowda et al, 2003) and other benzanilides (Gowda et al, 2008b). Further, the conformation of the amide oxygen in N35DMP2CBA is anti to the ortho-chloro group in the benzoyl ring similar to that observed in N35DCP2CBA but in contrast to the syn conformation observed in NP2CBA.…”
Section: Data Collectionsupporting
confidence: 69%